Tripping over parents: barriers to access to pharmaceuticalmedicines in the developing world and proposed solutions to enhance access within the WTO framework - Radfar, Naheed (Centre for Law and Society, 2026)
Four years after which members of the World Trade Organisation ("WTO") agreed upon a system by which developing countries could import generic versions of patented medicines produced without authorisation of patent holders to address public health needs, no country had yet spoken. 1 On July 19, 2007, Rwanda took a dramatic leap of faith to break the spell of silence and become the first and only country to inform the WTO of its intent to utilise those very procedures. Before Rwanda, no developing country had ever made use of compulsory licensing as a tool to address public health issues.